Murottal Qur'an Psychotherapy on Breast Cancer Survivors in South Sulawesi - Azriful, Azriful; Wahyuddin, Wahyuddin; Jusriani, Rini (Diversity: Disease Preventive of Research Integrity, 2023)
Indonesia is ranked 8th in Southeast Asia with a high cancer incidence, with a breast cancer proportion of 16.7%. Chemotherapy, which is usually done, has side effects and stress for breast cancer survivors, so a solution that has minimal side effects and is easy to do is needed. This study aims to assess the effect of murottal Qur'an psychotherapy on breast cancer survivors in South Sulawesi. This study was qualitative with a phenomenological study approach. The key informants were breast cancer survivors who were Think Survive Cancer Woman Support Group community members. Data were collected through observation, in-depth interviews, and documentation by triangulating sources, methods, and times. The reinforcing factor for doing murottal Al-Qur'an psychotherapy is family support, especially from husbands, health workers' support, and the support of fellow survivors. Through murottal Al Qur'an, the self-acceptance of survivors to carry out their duties and obligations as wives and mothers of their children become better. Murottal Al-Qur'an Psychotherapy positively impacts the stress level of breast cancer survivors. Murottal Al-Qur'an psychotherapy provides a sense of calm for breast cancer survivors so that it has a positive effect in reducing stress.